2020
DOI: 10.1016/j.pediatrneurol.2019.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training as Part of Musculoskeletal Management for Congenital Myopathy: Where Are We Now?

Abstract: Congenital myopathy is a heterogeneous group of muscle disorders characterized by muscle weakness and hypotonia. This condition is associated with a range of skeletal, respiratory, and ophthalmologic complications and requires a multidisciplinary therapeutic approach aimed at maximizing the function and independence of patients. One promising direction for therapeutic intervention is physical exercise rehabilitation, given its demonstrated ability to promote muscle and bone health of patients with a variety of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Multidisciplinary therapeutic approaches are emphasized, including those related to neurology, neonatology, pulmonology, gastroenterology, rehabilitation medicine, and orthopedic surgery [6,7,18,19]. The decision to conduct a diagnostic workup involving a muscle biopsy for infants with hypotonia is sometimes difficult owing to a few factors, including the general anesthesia required for invasive procedures, the risk of respiratory complications, and occasional non-specific results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multidisciplinary therapeutic approaches are emphasized, including those related to neurology, neonatology, pulmonology, gastroenterology, rehabilitation medicine, and orthopedic surgery [6,7,18,19]. The decision to conduct a diagnostic workup involving a muscle biopsy for infants with hypotonia is sometimes difficult owing to a few factors, including the general anesthesia required for invasive procedures, the risk of respiratory complications, and occasional non-specific results.…”
Section: Discussionmentioning
confidence: 99%
“…Although long-term survivors depend on a wheelchair, ventilator, and tube feeding, the disease course of XLMTM is relatively stable [1]. The critical roles of a multidisciplinary unit include encouragement of exercise training to maximize patients' motor function and independence as well as safe maintenance of feeding tubes and home ventilators [6,7]. In a cross-sectional study about a natural history of patients with XLMTM, all observed deaths were associated with respiratory failure [1].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a recent epidemiological study showed that daily walking alone is sufficient to reduce pneumonia-related mortality among older people who do not regularly engage in other exercise habits [88]. Physical activity and rehabilitation programs are widely recognized as a way to improve both general health and musculoskeletal status in patients with neuromuscular diseases, of which congenital myopathy is one of them [89]. In animal models of congenital myopathy (Duchenne Muscular Dystrophy, mdx), WBPA has been shown to improve skeletal muscle strength, reduce muscle damage and inflammatory phenotype, and improve myocardial function [73,90].…”
Section: Discussionmentioning
confidence: 99%
“…There are currently no disease-modifying drug interventions for ACTA1 disorders and "insufficient evidence on the effectiveness of different modes and intensities of exercise programs." 14 Participant 3 discharged from the NICU and had 1 outpatient PT/OT EI evaluation prior to losing all EI services at the start of the pandemic. The family waited 11 months to resume OT services, 18 months to find a physical therapist willing to drive 90 minutes each way for home visits, and 42 months to start speech-language pathologist services for a communication device.…”
Section: Participantmentioning
confidence: 99%